IMPLEMENTASI BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PADA PT PEMBANGKITAN JAWA BALI SURABAYA - Wibawa, Riza; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out and to analyze the strategy implementation by using balanced scorecard in order to measure the performance of management of a company so it is consistent with the mission and vision which want to be achieved. The research object is done by using PT Pembangkitan Jawa Bali Surabaya. The research method is done by using qualitative method which is the research procedure which generates the descriptive data in the form of written words or spoken of the observed behaviour. Based on the research result, the company has been using balanced scorecard as the strategy implementation instrument in order to measure the performance of management. The result of the analysis shows that balanced scorecard is the method which interprets vision, mission, and strategy in the strategy targets and the standard of performance in four perspectives i.e.: financial perspective which is measured by ROI has reached the target with the realization average is 2.84%, the profit growth level and the sales growth level show less good result with the realization average is (4.63)% and 7.65%. It is caused by the decrease of electric energy sales, the customer perspective is measured by using customers acquisition and customer retention show good result with the realization average is 6.04% and 94.99%, the internal business process perspective is measured by using new facility and service which is provided after the transaction shows that the capacity of the company is categorized as a good company, and the growth and learning perspective is measured by using the retention of employees and the training of employees shows a good result with the realization average is 4.89% and 67.85%. in order to find out the correlation between the perspectives from each measurement a strategy map is made. It can be concluded from the result of the analysis that balanced scorecard can be use as the strategy implementation instrument in measuring the performance of the management with financial and non-financial perspective.Keywords: Strategy Implementation, Balanced Scorecard, Management Performance Measurement.